Association between pleural plaques and coronary heart disease - Korhola, Ossi; Hiltunen, Asta; Karjalainen, Antti; Martikainen, Rami; Riihimäki, Hilkka (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'The aim of this study was to verify a clinical impression that patients with coronary heart disease disproportionately frequently have calcified pleural plaques. ' ' METHODS ': 'Chest X-rays were collected from 148 patients referred consecutively to the Helsinki University Central Hospital for coronary angiography and from 100 consecutive lung cancer patients seen at the same hospital. The radiographs were analyzed for the presence of calcified pleural plaques according to the classification the International Labour Office. A generalized linear model with binomial distribution and log link was used to estimate the relative risks and their 95% confidence intervals (95% CI). ' ' RESULTS ': 'The prevalence of calcified pleural plaques was 35% for the coronary patients and 19% for the lung cancer patients. Calcified pleural plaques were more common among the men than the women, and the risk increased with age. The relative risk of calcified pleural plaques, adjusted for age and gender, was 2.19 (95% CI 1.44-3.32) for the coronary patients as compared with the lung cancer patients. ' ' CONCLUSIONS ': 'Further studies with better information on past exposure to asbestos and other potential risk factors are warranted to confirm the observations and to examine whether the association between coronary heart disease and calcified pleural plaques is related to an etiologic or an individual susceptibility factor common to both of these conditions.
Keywords: asbestos exposure; coronary heart disease; etiology; lung cancer; pleural plaque; short communication; susceptibility